Gynecologic pathology services in low- and middle-income countries. Issue 7 (23rd November 2021) - Olkhov-Mitsel, Ekaternia; Lu, Fang-I; Gagliardi, Anna; Plotkin, Anna
Abstract : Objective: The International Gynecologic Cancer Society (IGCS) offers multidisciplinary conferences to underserved communities. Mentor pathologists have become an integral part of these tumor boards, as pathology services in low-to-middle-income countries are often inadequate and disjointed. The IGCS Pathology Working Group conducted a survey to assess barriers to quality pathology services in low-to-middle-income countries and identified potential solutions. Methods: A 69-question cross-sectional survey assessing different aspects of pathology services was sent to 15 IGCS Extension for Community Healthcare Outcomes (ECHO) training sites in Africa, Asia, Central America, and the Caribbean. Local gynecologic oncologists distributed the survey to their pathology departments for review. The responses were tabulated in Microsoft Excel. Results: Responses were received from nine training sites: five sites in Africa, two in Asia, one in Central America, and one in the Caribbean. There were no pathologists with subspecialty training in gynecologic pathology. Most (7/9, 78%) surveyed sites indicated that they have limited access to online education and knowledge transfer resources. Of the eight sites that responded to the questions, 50% had an electronic medical system and 75% had a cancer registry. Synoptic reporting was used in 75% of the sites and paper-based reporting was predominant (75%). Most (6/7, 86%) laboratories performed limited immunohistochemical stains on site. None of the sites had access to molecular testing. Conclusions: Initial goals for collaboration with local pathologists to improve diagnostic pathology in low- and middle-income countries could be defining minimal gross, microscopic, and reporting pathology requirements, as well as wisely designed educational programs intended to mentor local leaders in pathology. Larger studies are warranted to confirm these observations.